Development and initial validation of the Teaching Multiple School Subjects Role Conflict Scale (TMSS-RCS) - Iannucci, Cassandra; MacPhail, Ann; R. Richards, K. Andrew (European physical education review, 2019)
There is a need to better understand the reality of enacting dual teaching positions, or roles, within a school. Therefore, role conflict experienced by teachers who are tasked with concurrently teaching multiple subjects warrants further understanding. For example, teachers responsible for teaching physical education (PE) and another school subject(s). There is, however, currently no published instrument for measuring role conflict of this nature. The purpose of this study was to develop and validate the Teaching Multiple School Subjects Role Conflict Scale, an instrument to measure interrole conflict between the roles of teaching PE and another school subject(s). Research aims included: (a) developing the instrument; (b) identifying a factor structure for the instrument using exploratory factor analysis; (c) confirming the factor structure through confirmatory factor analysis; and (d) examining the correlation between the newly validated measure and conceptually similar (i.e. role stress) and dissimilar (i.e. resilience) constructs. Exploratory factor analysis identified a stable three-factor, nine-item solution, including schedule conflict, energy expenditure conflict, and status conflict. Confirmatory factor analysis supported this solution, χ2(24) = 47.16, p < 0.001, non-normed fit index = 0.950, comparative fit index = 0.967, standardized root mean square residual = 0.069, and root mean square error of approximation = 0.069. The newly validated scale correlated appropriately with conceptually similar and dissimilar constructs.